A model to assess the agility of manufacturing organisations: systems approach and application. (15th September 2011) - Saleeshya, P.G.; Babu, A. Subash; Vishnu, A.S.
To achieve the status of an agile manufacturer, organisations need to clearly understand the concept of agility related to their industrial and business circumstances and then identify and acquire the appropriate characteristics, which will result in an agile manufacturing organisation. This paper is related to a real-life study carried out in Indian manufacturing organisations to assess the extent to which the agile manufacturing paradigm is recognised and deployed, as this paradigm has been a major objective of many companies. With the help of literature study and a preliminary study of selected industries, a framework was developed which in its schematic form captures and depicts the efforts an organisation may have to put in a concerted manner to enhance its agility. This framework was used to develop a questionnaire with which a survey of Indian manufacturing industries was carried out. The data collected through this questionnaire was analysed by the model developed by the authors. This model helps to determine the measure of agility called effectiveness index for agility at the various hierarchical levels of an organisation. This paper reports the salient details of the model and how it was applied on the data collected from the industry survey.